Efektivitas Permainan Lompat Tali Karet untuk Meningkatkan Kemampuan Motorik Kasar pada Anak Tunagrahita Ringan di SLB Hikmah Reformasi, Padang - Auliani, Niza Fitria; Ardisal, Ardisal (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2019)
This research reveals that the child is mental retardation in the SLB of Hikmah Reformasi Padang that has problems with the rough motor capability that is the balance of the body when jumping. The research is aimed at finding out if the elastic rope jumping game is effective for enhancing the rough motor skills in the child is mental retardation. The research method used is Single Subject Research using A-B-A design. Tests given in the form of action tests are performing a rubber rope jumping game starting with standing upright, jumping with two legs as a rejection, the movement hovering in the air with both legs slightly attached, regulating the balance of the body when And the flexibility of the child in the jumping movement. Then the researcher conducting data analysis ie at A1 the initial condition of the rough motor ability of the child to obtain the result 22.22%, on condition B given the child treatment through the game of rubber rope jump obtained yield 88.88%. Next on condition A2 observations of child ability after not given the game (treatment) obtained the result 88.88%. From these results known children's abilities have improved using a rubber dance jumping game.